Automatic Generation of Optimized Integration Test Data by Genetic Algorithms - Pinte, Florin-Avram; Saglietti, Francesca; Oster, Norbert (Software Engineering 2008 - Workshopband, 2008)
The importance of software in nearly all of today’s engineering disciplines demands for development and validation techniques ensuring high dependability of complex software systems. Component-based software development as the ultimate approach for dealing with complexity shifts the focus of verification from unit to integration tests addressing the correctness of component interactions. As the current state-of-the-art does not include a systematic and tool-supported approach to interface testing, this paper presents a procedure for the automatic generation of integration test data based on genetic algorithms.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.lsinfs_1.automa